An analysis of factors to improve the capacity and value of older persons in Thailand - Thirapong Santiphop (2017)
The capacity and value of older persons is affected by physical activity and functional health factors. This study, based on a survey of 636 persons in Singburi, Pathum Thani and Nakhon Ratchasima provinces, applies logistic regression to analyze the factors influencing the value and capacity of older persons. Factor analysis identifies three significant factors: (1) physical activity (24% of variance); (2) functional health, which had high loading, variance and cumulative variance (32%); and (3) social functioning, which also had high loading, variance and cumulative variance (39%). Logistic regression found that heavy exertion (i.e., running fast, lifting heavy objects, and strenuous sports activity), gender, hypertension, faintness, wooziness and dizziness had positive predictive values, and these were statistically significant predictors of the current employment status of older persons. Heavy exertion, membership in a senior citizens group, gender and faintness, wooziness and dizziness, with statistically significant positive predictive values, were best able to predict the value of older persons as measured by their contribution to community services and assistance to their family. These findings suggest that improved capacity and value of older persons can be positively influenced by physical activity and functional health as well as social functioning factors.